The analysis of root canal curvature and direction of maxillary lateral incisors by using cone-beam computed tomography: A retrospective study. Issue 1 (7th January 2022) - Wang, Linlin; Wang, Zhensong; Wang, Qiang; Han, Jingchao; Tian, Hongsheng
Abstract : Abstract: The aim of this study was to investigate root canal curvature and direction of maxillary lateral incisors in Shandong, China. Cone beam computed tomography (CBCT) images of 176 maxillary lateral incisors of 88 patients were collected in Shandong Province, China. Software included with CBCT was used to measure the angle of root canal curvature of maxillary lateral incisors on the maximum bending plane. In addition, the direction of each root canal was recorded. The data were statistically analyzed by SPSS 17.0 software package. The results showed that all the samples had a single canal (Vertucci's type I). The incidence of straight root canals, curved root canals, and S-type root canals was 39.2%, 58%, and 2.8%, respectively. The difference in the mean angle of root canal curvature failed to identify any differences between the left and right side ( P  > .05). The most curved root canal of maxillary lateral incisors oriented in the palato-distal direction. The maxillary lateral incisors were mainly curved root canals of which the proportion of moderate curvature was the largest. Software included with CBCT would provide some valuable information for root canal instrumentation of maxillary lateral incisors.